Internet based monitoring of multivariable control using a quadruple-tank system for mechatronics education - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY PRESS, 2008)
The Internet has evolved into an environment for developing almost all kinds of applications. A computer and an Internet connection are all that is necessary to access information regardless of time or place. These have led to new approaches to teaching techniques. New teaching methods not restricted by time and place have been developed. Web based education is one of these systems. In this method of education, students work with simulations rather than actual systems. This paper presents the development of an Internet-based system to allow monitoring of important process variables from a commercial process system has been modified to a quadruple-tank setup to be used in mechatronics Process Control laboratory at Marmara University, Faculty of Technical Education.
Keywords: multivariable control; control education; quadruple-tank; remote monitoring